Strategi Pengembangan Program Kawasan Rumah Pangan Lestari (KRPL) di Kabupaten Tulang Bawang Barat - Pujiana, Tri; Rangga, Kordiyana K; Syarief, Yuniar A; Mutolib, Abdul (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
Sustainable Food Home Area is the concept of optimizing the use of yard locations around the house with a variety of plants, livestock, and fish in an area. The research objective is to determine internal and external factors and determine the strategy for developing a Sustainable Food Home Area program in Tulang Bawang Barat District. The research method used is a quantitative method. Data on internal and external environmental factors in this program were collected through observation, interviews with respondents with the help of questionnaires, in-depth interviews, and documentation studies. Data was collected in December 2019. The strategy program for the development of Sustainable Food Home Area in Tulang Bawang Barat Regency was analyzed using SWOT analysis. The recommended model for developing the program is based on the results of the assessment and analysis of natural and environmental resource potential and the potential of the program which is integrated with an analysis of the socio-economic, protection, and partnership aspects of its development. The results of the analysis of the internal factors are a) strengths (geographical position, around to production input providers and consumers, as well as the bargaining position to consumers), and b) Weakness (Human Resources, managers and assistance, the influence of pests and diseases, and the use of technology in the implementation program). External factors are c) Opportunities (policies in developing programs, government support, supporting infrastructure, and safety performance and capacity), and d) Threats (use of modern technology, collaboration with companies, cooperation, increases in prices of other products, and impact and changing weather). The priority strategy improvement program can be carried out by increasing savings by increasing compatibility, optimizing the function of the yard to increase the amount of production, increasing the bargaining position by providing quality products for profit, and marketing products by utilizing existing infrastructure.